2013
DOI: 10.3989/ajbm.2351
|View full text |Cite
|
Sign up to set email alerts
|

Not only size matters: achene morphology affects time of seedling emergence in three heterocarpic species of <i>Anacyclus</i> (Anthemideae, Asteraceae)

Abstract: Torices, R., Agudo, A. & Álvarez, I. 2013. Not only size matters: achene morphology affects time of seedling emergence in three heterocarpic species of Anacyclus (Anthemideae, Asteraceae). Anales Jard. Bot. Madrid 70(1): 48-55.The production of two or more distinct fruit types by an individual, i.e. heterocarpy, is considered as a mixed dispersal strategy in which a proportion of the offspring is able to colonize new sites, whilst others remain near the maternal location. Here, we aimed to explore the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 61 publications
(80 reference statements)
3
26
1
Order By: Relevance
“…A detailed analysis in A. valentinus by the ovule donor (not shown) suggested maternal effects as the source of variation (i.e., fertility varied depending on the ovule donor rather than on population). The results of germination tests showed high success in all cases (>75%, n = 691) and were similar to those obtained in natural populations (Torices et al., ), 98% survived, of which 98.5% developed flowers, and only 0.7% did not produce pollen.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…A detailed analysis in A. valentinus by the ovule donor (not shown) suggested maternal effects as the source of variation (i.e., fertility varied depending on the ovule donor rather than on population). The results of germination tests showed high success in all cases (>75%, n = 691) and were similar to those obtained in natural populations (Torices et al., ), 98% survived, of which 98.5% developed flowers, and only 0.7% did not produce pollen.…”
Section: Resultssupporting
confidence: 85%
“…Sampling and sowing was previously described in Torices et al. (). After germination, seedlings were grown individually in a mix of COMPO SANA ® Universal Potting Soil (COMPO GbmH, München, Germany) and siliceous sand (3:1) until the first 4 to 6 leaves developed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Torices et al . ). Given that ecological studies on germination speed have suggested a strong relationship with seed size and competitiveness (Dubois & Cheptou ; Lonnberg & Eriksson ; Afonso et al .…”
Section: Discussionmentioning
confidence: 97%
“…Both species are interfertile and self‐incompatible (Humphries, ; Agudo, ), and bloom from February to July. After fertilization, flowering heads from both species produce two types of achenes, i.e., one‐seeded dry fruits: flowers at the outermost positions, including both ray and disc outermost florets, produce winged and heavier achenes, whereas the innermost disc flowers produce lighter unwinged achenes (Torices et al., ; Afonso et al., ).…”
Section: Methodsmentioning
confidence: 99%